Determinants of transport mode choice in the Austrian province of Vorarlberg. - Ashrafi, Seyedeh R.; Neumann, Hans-Martin (My University, 2017)
Die Faktoren, die das Mobilitätsverhalten von Menschen bestimmen, sind relativ vielfältig. Neben Faktoren wie Stadtform und Verkehrsinfrastruktur beinflussen persönliche Faktoren die Verkehrsmittelwahl stark. DieseTatsache ist von Bedeutung für die Siedlungsentwicklung und Verkehrsplanung. Der Beitrag untersucht den Einfluss soziodemografischer und geographischer Faktoren auf die Verkehrsmittelwahl im österreichischen Bundesland Vorarlberg. Die Ergebnisse zeigen, dass die Haushaltsgröße, das Alter, das Geschlecht, das Einkommen und die Reisemotivation einen signifikanten Einfluss auf die Wahl der Verkehrsmittel haben.

Almost all countries have policies to reduce the usage of private car and to raise the usage of public transport by reducing the distance of travel, increasing density, increasing the access to public transport and so on. All of these developments are effective strategies for reducing car dependency. The factors which determine travel behavior of people are relatively broad. Besides the factors such as urban form and transport infrastructure, one important factor is the personal attribute which has a strong effect on the modal choice. By better understanding of this fact, the settlement development and transport planning can be integrated in a more sustainable way. This paper addresses the influence of socio-demographic and geographic factors on the selection of mode choice in the Austrian province of Vorarlberg. Result show that the household size, age, gender, income and motivation of travel have a significant effect on the modal choice.
Keywords: Verkehrsmittelwahl; Verkehrsplanung; Einflussfaktor